Purification of Raw Water from Pollutant using Coupling Membrane Filtration to UV Irradiation: Preliminary Study - Dhias Cahya Hakika; Zahrul Mufrodi; Shinta Amelia (Universitas Ahmad Dahlan, 2022)
The low quality of groundwater, along with the increasing demand for drinking water for the community, encourages the need for water treatment technology to produce quality drinking water that is environmentally friendly. One promising method to be applied is membrane technology. In water treatment systems, membrane technology is often not used alone but combined with other methods to improve water quality more effectively. This study aims to apply several methods for the raw water treatment system to drinking water, including membrane filtration and UV irradiation. The removal of chemical pollutants was investigated and compared to the standard value from Minister of Health Regulation No. 492 Year 2010 for drinking water quality. This coupled treatment successfully improved the water quality. The concentration of chemical and biological pollutants such as total dissolved solids (TDS), Fe, Zn, Pb, and total Coliform were reduced by 58.53%; 43.48%; 88.89%; 66.67%.; and 86.15%, respectively. The results indicate that coupling microfiltration membrane to UV irradiation method can be an effective treatment to remove chemical pollutants and enhance the quality of raw water for drinking water preparation.